2017
DOI: 10.1002/ccr3.908
|View full text |Cite
|
Sign up to set email alerts
|

Severe neutrophilic leukocytosis as a progression marker in granulocyte colony‐stimulating factor‐producing squamous cell carcinoma of the esophagus

Abstract: Key Clinical MessageThere are very few reports of esophageal carcinoma producing granulocyte colony‐stimulating factor (G‐CSF). G‐CSF‐producing esophageal squamous cell carcinoma is an extremely aggressive carcinoma. Leukocyte counts, neutrophil counts, and serum C‐reactive protein levels may be markers of its progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Two cases and one case of G-CSF-producing gastric cancer were histologically diagnosed as adenosquamous carcinoma and undifferentiated carcinoma, respectively. Among the 21 described cases, neutrophil infiltration in the tumor was observed in only two cases of G-CSF-producing esophageal cancer (16,25). However, no specific morphological features were found.…”
Section: Discussionmentioning
confidence: 97%
“…Two cases and one case of G-CSF-producing gastric cancer were histologically diagnosed as adenosquamous carcinoma and undifferentiated carcinoma, respectively. Among the 21 described cases, neutrophil infiltration in the tumor was observed in only two cases of G-CSF-producing esophageal cancer (16,25). However, no specific morphological features were found.…”
Section: Discussionmentioning
confidence: 97%
“…Increasing evidence has indicated that some types of established cancers may actually accelerate the process of myelopoiesis, resulting in moderate, or even profound, leukocytosis, characterized by increased numbers of immature myeloid cells in the bone marrow, blood and spleen [25][26][27][28][29]. In this setting, accelerated myelopoiesis appears to result from the production of bone marrow-stimulating growth factors by tumor cells, most notably the cytokines granulocyte colony-stimulating factor (G-CSF) and granulocyte/macrophage colony-stimulating factor (GM-CSF) [30][31][32][33][34][35]. In this context, it is noteworthy that an increased circulating neutrophil/lymphocyte ratio (NLR, defined as the absolute circulating neutrophil count divided by the lymphocyte count) is widely regarded as being a negative prognostic indicator in many, but not all, types of cancer reviewed in [36].…”
Section: Recruitment and Exploitation Of Neutrophils By Tumorsmentioning
confidence: 99%
“…A review of the medical literature in English revealed 19 case reports associated with esophageal squamous cell carcinoma [ Table 1] [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. All the cases have occurred in Japan.…”
Section: Discussionmentioning
confidence: 99%